SISTEM PERTANIAN KEBUN CAMPURAN BERKELANJUTAN BERBASIS TEKNOLOGI TRADISIONAL Studi Kasus Pada Masyarakat Krui Lampung Barat - Juhadi, Juhadi (Faculty of Social Science, Universitas Negeri Semarang, 2013)
This paper examines the role of local communities in land resource management. The question attempted to answer is, why the presence of damar agroforest in Krui villages continues from generation to generation? Data and information of this paper is the result of field research in Krui community, West Lampung. Data collection is carried out by means of participant observation and in-depth interviews with informants and documentation study of previous writings. The results showed that the presence of damar agroforest is very closely related to technology (traditional) which is owned, understood and practiced by the locals for generations. All matters relating to the use and management of damar agroforest done by calculation and careful consideration, especially in the acquisition of land, planting, maintenance and harvesting so damar agroforest continue to contribute both economically and ecologically.